Optimalisasi Program KALIMASADA Melalui Aplikasi Klampid New Generation (KNG) Bersama MSIB Batch 4 Di Kelurahan Wonokromo - Pramudita, Della Widya; Nur, Dhani Ichsanuddin (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
The Surabaya City Government and the Surabaya City Population and Civil Registry Office are innovating to make the people of Surabaya City aware and more obedient to the importance of population administration. Population administration is the arrangement and issuance of population data and documents through population registration, civil registration, and management of population information whose results are used for public services, government and development. The innovation made by the government and the City of Surabaya Population and Civil Registry Office in dealing with the issues described above was through the initiation of the KALIMASADA (Population Administration Aware Environmental Area) program. This program is promoted to provide more effective and efficient public services. The author served as a companion for administrative services in the Wonokromo Village. The method used in the preparation of this devotional journal is by means of a direct approach through the assistance of the RT head and the community in the Wonokromo Village regarding administration and the use of the KNG application